Robust Optimal Dispatching of Wind Fire Energy Storage System Based on Equilibrium Optimization Algorithm - Chen, Xiaojiao; Huang, Liansheng; Zhang, Xiuqing; He, Shiying; Sheng, Zhicai; Wang, Zhenshang; Chen, Tao; Dou, Sheng (Frontiers in Energy Research, 2021)
The uncertainty of wind resources is one of the main reasons for wind abandonment. Considering the uncertainty of wind power prediction, combined with advanced adiabatic compressed air energy storage (AA-CAES) technology, a robust optimal dispatching model is proposed for the wind fire energy storage system. Herein, the operation constraints of the power plant and constraints of the reserved capacity are defined according to the operation characteristics of AA-CAES. Based on the limited scenario method, a solution framework is proposed to achieve the optimal robustness and economical operation of the system, providing a new way for the application of the intelligent algorithm in the robust optimal dispatching. Specifically, a novel equilibrium optimization algorithm is presented to solve the optimal dispatching problem, which has good global search performance. The proposed solution is validated through simulations based on the IEEE-39 node system. The simulation results verify the effectiveness of the proposed dispatching model and the intelligent solver.